2023
DOI: 10.1007/s12144-023-04593-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of teacher’s emotional intelligence on team-member exchange and job performance: the moderating role of teacher seniority

Abstract: This study aims to examine the effects of teachers’ seniority, emotional intelligence (EI), and team-member exchange (TMX) quality on their job performance in primary schools. In particular, the mediating role of TMX on the relationship between EI and job performance, and the moderated mediating effect of teacher seniority on EI-TMX-job performance relationships were scrutinised. Data were collected from 387 teachers of primary schools in Taiwan. The SPSS PROCESS macro and structural equation modelling (SEM) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…, 2007; Lu and Chen, 2023). It was found that teachers' in-role job performance is higher than their extra-role job performance (Lu and Chen, 2023). Li et al.…”
Section: Conceptual Frameworkmentioning
confidence: 98%
See 2 more Smart Citations
“…, 2007; Lu and Chen, 2023). It was found that teachers' in-role job performance is higher than their extra-role job performance (Lu and Chen, 2023). Li et al.…”
Section: Conceptual Frameworkmentioning
confidence: 98%
“…For example, middle leaders proactively reflect the opinions of communities to the school. These two elements of job performance have been transferred into the educational setting to evaluate teacher's job performance in the Taiwan context (Chen et al, 2007;Lu and Chen, 2023). It was found that teachers' in-role job performance is higher than their extra-role job performance (Lu and Chen, 2023).…”
Section: Job Performancementioning
confidence: 99%
See 1 more Smart Citation
“…For women educators, who often navigate complex interpersonal relationships and diverse student needs, emotional intelligence is especially crucial [35]. It enables them to empathize with their students, understand their perspectives, and effectively manage classroom conflicts [36].…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Naz et al [44] further presented evidence to support the theory that employees with higher EI display professionalism in interpersonal relations, stress management, activity scheduling, and leadership acumen, which ultimately enhances their performance in a team. This implies that interpersonal skills and adaptability are crucial abilities that help employees perform optimally either solely or within a group [4,8,33]. [25] opined that EI plays an even more important role at the managerial level as a demonstration of a high level of self-emotion management by a leader engenders a productive workplace characterised by selfless relations that motivate individuals to deliver at their best.…”
Section: Emotional Intelligence and Job Performancementioning
confidence: 99%